Comparative analysis of VMAT plans on Halcyon and infinity for lung cancer radiotherapy - Kainan Shao; Fenglei Du; Lingyun Qiu; Yinghao Zhang; Yucheng Li; Jieni Ding; Wenming Zhan; Weijun Chen (PLoS ONE, 2025)
Objective The dosimetric characteristics and treatment efficiency of VMAT plans using two linear accelerator platforms, Halcyon and Infinity, in conventional radiotherapy for non-small cell lung cancer (NSCLC) are compared to provide data for selecting clinical equipment. The study also explores potential confounding factors that may influence treatment outcomes. Methods This retrospective cohort study aims to compare the dosimetric characteristics and treatment efficiency of VMAT plans delivered using Halcyon and Infinity linear accelerator platforms in patients with NSCLC. A retrospective analysis was performed on 60 NSCLC patients receiving conventional fractionated radiotherapy with VMAT plans developed for both Halcyon and Infinity. These plans were optimized with RayStation 9A with identical dose constraints and optimization parameters. The groups were compared in terms of target dose coverage, normal tissue sparing, plan complexity, and treatment efficiency. The dosimetric parameters included D98%, D2%, and Dmean for both the CTV and PTV and dose distributions for organs at risk (OARs), including the heart, lungs, and spinal cord. Logistic regression was performed to account for potential confounding factors, such as PTV volume, tumor stage, and tumor location. Results The VMAT plans of both platforms met the clinical dosimetric requirements. Halcyon showed superior protection of normal tissues in low-dose areas (e.g., Lungs V5Gy and Heart V30Gy), whereas Infinity excelled in controlling hot spots and achieving rapid dose fall-off at the target margins. Furthermore, Halcyon has fewer plan monitoring units and lower complexity than Infinity and reduced treatment time by 24.0%. Logistic regression analysis revealed that PTV volume was a significant predictor for dose metric differences, while tumor stage and tumor location had variable effects depending on the dose metric, highlighting the need to account for these factors in clinical comparisons. Overall, there was no significant difference in target dose coverage or uniformity between the platforms; each demonstrated specific strengths in protecting different OARs and in treatment execution efficiency. Conclusion Halcyon and Infinity offer distinct advantages in radiotherapy for NSCLC. Halcyon provides better protection of normal tissues and performance in low-dose regions, whereas Infinity offers greater treatment efficiency and superior control in high-dose regions. The study also highlights that PTV volume is an important factor influencing dosimetric outcomes. In choosing optimal radiotherapy equipment in clinical practice, the study results suggest that treatment planning should leverage the unique technical features of different accelerators to achieve the best individualized outcomes. Future studies should increase the sample size and employ prospective research designs to confirm the clinical relevance of these findings.